Does the severity of interstitial lung disease affect the gains from pulmonary rehabilitation?. (24th March 2018) - Deniz, Sami; Şahin, Hülya; Yalnız, Enver
Abstract: Introduction: Reduced exercise capacity is a main feature of Interstitial Lung Diseases (ILDs) and it is related to closely prognosis of these patients. Pulmonary Rehabilitation (PR) results to improve in peak exercise capacity, dyspnea and quality of life in ILDs. Objectives: We aimed to evaluate the benefits of PR in patients with ILDs and to determine whether there are similar gains in patients with severe ILD. Methods: We recruited ILD stable patients. All patients were evaluated with pulmonary function test, exercise capacity [6‐minute walking test (6MWD)], quality of life [Short Form‐36 (SF‐36), St. George's Respiratory Questionnare (SGRQ), Hospital anxiety and Depression (HAD)] before and after PR (8 week). Results: Fifty‐seven patients who completed PR program, 30 women and 27 men, included in this study. It was determined a significant difference in terms of quality of life and exercise capacity ( P  < .05) before and after PR. When these patients were divided into 2 groups (DLCO <40% predicted, severe: group‐1, and group‐2: other ≥40], there was no difference between 2 groups except for forced expiratory volume in 1 second, pulse oxygen saturation and partial oxygen pressure (pO 2 ). When compared the differences between pre and post values of all variables, there was no difference significantly except 4 variables (SF‐36; physical functioning, social functioning, role physical and pO2 ). Conclusion: PR led to improvement in quality of life and exercise capacity in ILDs. In addition, PR, irrespective of the severity of the disease, is particularly beneficial in patients with severe ILDs.